2006
DOI: 10.1101/gad.1493306
|View full text |Cite
|
Sign up to set email alerts
|

A PHD finger protein involved in both the vernalization and photoperiod pathways in Arabidopsis

Abstract: The proper timing of flowering is critical for successful reproduction. The perception of the seasonal cues of daylength changes and exposure to cold influences flowering time in many plant species through the photoperiod and vernalization pathways, respectively. Here we show that a plant homeodomain (PHD) finger-containing protein, VIN3-LIKE 1 (VIL1), participates in both the photoperiod and vernalization pathways in Arabidopsis thaliana by regulating expression of the related floral repressors FLOWERING LOCU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
269
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(278 citation statements)
references
References 28 publications
7
269
1
1
Order By: Relevance
“…For example, phyB, dnf, spa1 and cop1 flower early, whereas vil1, vil2 and a gain-of-function mutation in IAA7/AXR2 (axr2-1) flower late specifically under SD conditions (Ishikawa et al, 2006;Kim and Sung, 2010;Laubinger et al, 2006;Mai et al, 2011;McNellis et al, 1994;Morris et al, 2010;Reed et al, 1993;Sung et al, 2006). However, vil1, vil2 and axr2-1 mutants display quantitative differences in flowering time compared with the wt and still flower under SD conditions (Kim and Sung, 2010;Mai et al, 2011;Sung et al, 2006). Although the ga1 mutant also failed to flower under SD, ga1 flowers significantly later under LD as well (Michaels and Amasino, 1999b;Wilson et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, phyB, dnf, spa1 and cop1 flower early, whereas vil1, vil2 and a gain-of-function mutation in IAA7/AXR2 (axr2-1) flower late specifically under SD conditions (Ishikawa et al, 2006;Kim and Sung, 2010;Laubinger et al, 2006;Mai et al, 2011;McNellis et al, 1994;Morris et al, 2010;Reed et al, 1993;Sung et al, 2006). However, vil1, vil2 and axr2-1 mutants display quantitative differences in flowering time compared with the wt and still flower under SD conditions (Kim and Sung, 2010;Mai et al, 2011;Sung et al, 2006). Although the ga1 mutant also failed to flower under SD, ga1 flowers significantly later under LD as well (Michaels and Amasino, 1999b;Wilson et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…For example, plant homeodomain finger-containing proteins such as VIN3-LIKE 1 and 2 [VIL1 (also known as VRN5) and VIL2] have been shown to promote flowering through epigenetic repression of MAF1 and MAF5 genes, respectively, under SD conditions (Kim and Sung, 2010;Sung et al, 2006). vil1 and vil2 mutants flower later only under SD conditions, but do eventually flower.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of VIN3-like proteins focused on their roles in vernalization of Arabidopsis and wheat [28,29]. Arabidopsis VIN3 is a component of the polycomblike protein complex and is responsible for vernalizationmediated repression of the FLC gene, and vin3 mutant shows the late-flowering phenotype only after vernalization [42].…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis VIN3 is a component of the polycomblike protein complex and is responsible for vernalizationmediated repression of the FLC gene, and vin3 mutant shows the late-flowering phenotype only after vernalization [42]. VIN3-LIKE 1 (VIL1) participates in both the photoperiod and vernalization pathways [28], suggesting the critical role of VIN3-like proteins in regulation of flowering [28,42,43]). In this study, we showed that spontaneous mutants of LC2, a rice homolog of Arabidopsis VIN3, present the late-flowering phenotype, suggesting that even in rice, a nonvernalized plant, the VIN3-like protein also participates in flowering time control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation